Expanding the Phenotype of TRMT10A Mutations: Case Report and a Review of the Existing Cases - Zeynep Şıklar; Tuğba Kontbay; Kevin Colclough; Kashyap A. Patel; Merih Berberoğlu (Galenos Yayincilik, 2023)
The tRNA methyltransferase 10 homologue A (TRMT10A) gene encodes tRNA methyl transferase, and biallelic loss of function mutations cause a recessive syndrome of intellectual disability, microcephaly, short stature and diabetes. A case with intellectual disability and distinctive features including microcephaly was admitted. She was diagnosed with epilepsy at 2.5 years old. At 3.6 years of age, severe short stature related to growth hormone (GH) deficiency was detected. She had an incidental diagnosis of diabetes at age 11.4 years which was negative for diabetes antibodies with persistent C-peptide level and she was treated with metformin. Spontaneous puberty did not begin until 15.7 years of age and she was found to have primary ovarian failure. A homozygous p.Arg127* mutation in TRMT10A was detected. In addition to the typical clinical features which characterize TRMT10A syndrome, we observed an unusual form of impaired glucose metabolism which presented in early childhood with hypoglycemia followed by diabetes in late childhood. GH deficiency and primary ovarian failure may also be additional findings of this syndrome. Patients with slow onset diabetes who are negative for autoantibodies and have extra-pancreatic features should be tested for all known subtypes of monogenic diabetes.